Evaluation of Body Composition and Quality of Life of University Students - Sahin, Suleyman; Sahin, Senay; Yildirim, Duygu; Kirkaya, Izzet (Asian Journal of Education and Training, 2019)
The aim of this study is to evaluate the physical activity levels and the quality of life of the university students. In this purpose, the SF-36 life quality scale was used to examine the quality of life of the participants and physical activity levels were also determined through IPAQ. One-way ANOVA was used to compare the quality of life based on the physical activity levels of the participants. Moreover, the Bonferroni Correction were used to determine which physical activity level causes the difference by keeping the type I error rate fixed at 0.05. Statistically significant results were observed between social function and physical activity levels for the female group. In addition, statistically significant results were found between vitality and physical activity levels for the male group. The results show that there is a significant relationship between physical activity and quality of life. The individuals who feel more fit and social tend to have an active life. Given that it is crucial to intensify the studies on this topic for university students to encourage them for taking up regular physical activity as a part of life style.